IMPLEMENTASI LAYANAN JARINGAN PEMECAHAN MASALAH E-MODUL BERBASIS MOBILE SEBAGAI MEDIA ALTERNATIF - Sirwan Sirwan; kamal kamal (Akademika, 2020)
The purpose of this study was to: (1) knowing the level of practicality e-module based on mobile learning; (2) determine the effectivenes of using system e-module based on mobile learning in skill competency test TKJ. The research method experimental design one group pre-test and post-test. Data were collected through multiple choice test given to respondens before being given treatment and after being given treatment, then the data would then be analyzed using tes t. The results of the e-module practicality test throught a questionnaire distributed to students showed that the e-module based on mobile learning practicality used by students, while according to the assessment by the two media experts that e-module based on mobile learning was practical with an average score of 88.9%. Student readiness in UKK has been successfully improved using mobile learning-based e-modules. Increased readiness of students in UKK is in the medium category with a gain score of 0.4%. The T test results indicate that the Sig. (2-tailed) of 0.000 <0.05. The mean pre-test value was 78.6456 with Std.Deviation 4.85293. The highest value is 90.00 and the lowest value is Std.Deviation 6.57910. The highest score was 96.67 and the lowest score was 73.33.